Design of a dual band planar inverted-F antenna for GMS/DCS mobile handset - Fang, Jun (2008)
This project involved the study of size miniaturization of microstrip antenna techniques: shorting pin and shorting wall, loading, shorted spiral printed antenna and stacked shorted patch antenna are fully discussed.